Main Challenges in Structural Drainage: A Perspective Based on Contemporary Global Literature - Maia, Joyce; Cattani, Yan Nonato; Paula , João Gabriel de; Christofidis, Demetrios; Kuwahara, Monica Yukie (ANAP Brazil, 2025)
ABSTRACT Objective: This study aims to identify the main challenges in implementing structural measures for stormwater drainage. Methodology: An integrative literature review and content analysis were performed. Originality/Relevance: The study addresses the inability of traditional drainage approaches to cope with the challenges of climate change, highlighting several types of infrastructure, control measures, and the need for original approaches to stormwater drainage. Results: A total of 131 articles were selected for analysis, with English being the predominant language. The literature showed an increase in publications starting in 2017, with a peak in 2020. Green infrastructure was the most discussed topic, followed by gray infrastructure and, finally, blue. The most recurrent themes were performance evaluation and economic assessment. Theoretical/Methodological Contributions: This study contributes by consolidating nature-based solutions and hybrid arrangements as central strategies for sustainable urban drainage. It also points out that the transition to hybrid models, which combine distinct types of infrastructure, is an irreversible trend. Social and Environmental Contributions: The analysis highlights that drainage is the most fragile aspect of basic sanitation in Brazil, with a high geohydrological risk. The work underscores the need to prioritize drainage in public policies, considering that a generous portion of municipalities lack specific pluvial systems and expert plans.